FUNGSI GENDING AYAK WOLU PADA WAYANG KULIT GAGRAG JAWA TIMURAN KI SURWEDI - Jepri Ristiono (Institut Seni Indonesia Surakarta, 2019)
ABSTARCTÂ This article originated from the interest of the author when he saw the phenomenon that occurred in the East Javanese leather puppet show Ki Surwedi, especially gending Ayak pathet Wolu which is very dominating. The discussion is focused on the gending function of Ayak pathet Wolu which concerns the relation of the song with the gamelan, so that it can conclude about the role and function of the song. Therefore, this article is qualitative with priority on the form of interview data and literature, and presented in descriptive-analytic. The data collected from various sources was analyzed using the function theory initiated by Alan P. Merriam in a book entitled The Anthropology of Music, translated by Hajizar in the form of